2017
DOI: 10.1097/aog.0000000000001972
|View full text |Cite
|
Sign up to set email alerts
|

Maternal, Fetal, and Neonatal Imatinib Levels With Treatment of Chronic Myeloid Leukemia in Pregnancy

Abstract: Imatinib is effective for CML in pregnancy, but caution is warranted in light of potentially unrecognized fetal and neonatal effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…However, more recently it has been suggested that TKIs may be safe for use in the second or third trimester of pregnancy. Burwick and colleagues recently reported treatment of CML in pregnancy with imantinib initiated at the end of the second trimester, with no adverse outcome, despite high concentrations of imantinib being demonstrated in the neonate's urine. Unfortunately, large‐scale clinical studies confirming the safety of TKIs later in pregnancy are lacking, and there is a paucity of data regarding the use of bosutinib and ponatinib in that setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recently it has been suggested that TKIs may be safe for use in the second or third trimester of pregnancy. Burwick and colleagues recently reported treatment of CML in pregnancy with imantinib initiated at the end of the second trimester, with no adverse outcome, despite high concentrations of imantinib being demonstrated in the neonate's urine. Unfortunately, large‐scale clinical studies confirming the safety of TKIs later in pregnancy are lacking, and there is a paucity of data regarding the use of bosutinib and ponatinib in that setting.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been challenged by the observation of hydrops fetalis in a woman who started dasatinib in the second trimester, 29 and supported by reports of detection of TKIs and their metabolites in cord blood, placental tissue, amniotic fluid, fetal plasma and neonatal urine. 9,16 It is therefore reasonable to avoid TKIs throughout pregnancy. If treatment is required then the options include leucapheresis, interferon and TKIs.…”
Section: Female Patientsmentioning
confidence: 99%
“…The authors summarized information from 26 cases of imatinib use during pregnancy and noted no fetal abnormalities when the drug was started beyond the second trimester. A subsequent report by Burwick et al 28 described the use of imatinib at 28 weeks’ gestation for CML diagnosis in pregnancy, after failure of leukapheresis and IFN; complete hematologic response was achieved within 4 weeks. Normal childbirth was observed despite detection of residual levels of imatinib in placental tissue and amniotic fluid.…”
Section: Diagnosed During Pregnancymentioning
confidence: 99%